The Basic Rheological Properties of LDPE Modified Bitumen - Sudibyo, Tri; Suwarto, Fardzanela; Fauzan, Muhammad; Arif, Chusnul (Departemen Teknik Sipil dan Lingkungan IPB, 2024)
Various polymers have widely known in its capability in enhancing rheological properties of bitumen for various pavement applications. Many polymer types have been used in studies, where the properties of the final product of the polymer modified bitumen (PMB) are different, depending on the used polymers. LDPE or Low-Density Polyethylene are one of widely studied polymers in bitumen modification that exhibit higher bitumen's viscosity, perform better in resisting deformation under heavy loads, and tend to show better integrity in high temperatures. LDPE-modified bitumen also believed to enhance elasticity, allowing a potentially better resistance to cracking due to ability to recover at low strain. Many studies also stated the improvement of LDPE-modified bitumen against thermal and mechanical stress, better adhesion to aggregates in asphalt mixtures, and various promising result for overall durability and longevity of pavement. This study explains basic rheological properties of LDPE-modified bitumen prepared by high shear mixing and specified preparing methodologies. Five variables of %modifications were used: 2%, 4%, 6%, 8% and 10% of bitumen weight. Ring and Ball softening point, Penetration test and rotating spindle viscometry were done to understand the rheological changes of the modified bitumen compared to unmodified bitumen control. For further understanding the behaviour, two types of LDPE were used: virgin LDPE and recycled LDPE. The study shows interesting noticeable differences between the two used LDPE polymers, allowing further proposed studies in this field.